EVALUASI IMPLEMENTASI KEBIJAKAN PENERIMAAN PESERTA DIDIK BARU SISTEM ZONASI - Kosasih Ali Abu Bakar; Yetti Supriyati; Ivan Hanafi (Akademika, 2020)
The policy for admitting new students with this zoning system is based on the proximity of the student's residence to the school, so that indicators of student capacity and the quantity of students in the zoning area are the most important. This study aims to determine the extent of the success of the implementation of the new student admission policy by analyzing the factors that influence the success of this policy. This research uses mixed methods, this research is a qualitative research supported by quantitative research. The research stage begins with the identification of issues / problems and mapping the problems from the mass / online media, the results of existing studies and the results of monitoring and evaluation and studies conducted by the Ministry of Education and Culture, after which it is continued with a survey. The researcher then conducted a discussion which resulted in policy options and recommendations and standard operating procedures in policy implementation for the socialization stage by taking into account the communication factor, the policy formulation stage by taking into account the commitment factor, and the policy implementation stage with due regard to resource factors and organizational structure factors. In addition, this study also identifies current policy implementation models and proposes recommendations that should be implemented.